Detection of Chlamydia trachomatis, Mycoplasma hominis and Ureaplasma urealyticum by Multiplex PCR in Semen Sample of Infertile Men - M Golshani; G Eslami; Sh Mohhammadzadeh Ghobadloo; F Fallah; H Goudarzi; AA Soleimani Rahbar; F Fayaz (Tehran University of Medical Sciences, 2007)
Background: The aim of this study was to detect Chlamydia trachomatis, Mycoplasma hominis and Ureaplasma urealyti¬cum from semen samples of infertile men by Multiplex PCR and investigation of influence of bacteriospermia on semen parame¬ters. Methods: Semen samples of 200 infertile men were evaluated by Multiplex PCR. In addition, analysis of semen parameters was performed according to the WHO guidelines. Results: All the patients were without clinical symptoms of urogenital tract infection. Thirty three percent of cases showed at least one bacterium. We found a noticeable relation between the presence of bacteriospermia and the rate of non motile and morphologically abnormal sperms (P< 0.0001). In addition, sperm concentration was lower in positive cases (P< 0.04). There was no relation between leukocytospermia and bacteriospermia (P> 0.05). Conclusion: Asymptomatic existence of Chlamydia and Mycoplasmas in urogenital tracts might play an important role in sperm impairment due to infertility. Bacteriospermia can influence sperm's motility, morphology and concentration.